Effect of Indium Contents on the Solution-Processed SiInZnO Thin Film Transistors Annealed at Low Temperature - Park, Ki-Ho; Chong, Eugene; Ju, Byeong-Kwon; Lee, Sang Yeol (ELECTROCHEMICAL SOC INC, 2011)
The effect of the indium contents (from 1 to 5 molar ratios of In) on the threshold voltage (V-th) and field effect mobilities (mu FE) of solution processed silicon-indium-zinc-oxide (SIZO) thin film transistors (TFTs) have been reported. The negative shift of V-th was occurred from 4.37 to -0.75 V and the mu FE was increased clearly by mainly exceeded In contents due to the increase of carrier concentration, which is related the increased of the number of free electrons associated with excess In incorpoation in the SIZO TFTs. As increasing the In content, the excess In affects films formation of SIZO and leads to decrease of surface roughness. Subthreshold swing (S.S) was decreased due to reduced trap density at the interfaces between the active channel layer and the insulator with decreasing surface roughness of the SIZO films. This proposed that the characteristics of SIZO TFTs can be improved by controlling the In molar ratio in the SIZO based TFTs. (C) 2011 The Electrochemical Society. [DOI: 10.1149/2.017112esl] All rights reserved.
Keywords: AMORPHOUS OXIDE SEMICONDUCTORS; CARRIER TRANSPORT